(untitled) (Stamford Journal of Microbiology, 2023)
Antibiotic resistance is a global concern that has emerged in recent years due to inappropriate and indiscriminate use of antibiotics. It is important to follow the changes in this antibiotic resistance for the sake of better treatment and patient management. The aim of this study was to collect clinical isolates from some renowned diagnostic centers and to determine their susceptibility patterns in different age and sex groups of patients. Clinical samples from a number of patients with various infectious symptoms were selected and microbiologically analyzed. Antibiotic resistance patterns for 15 different antibiotics Amikacin, Azithromycin, Ciprofloxacin, Ceftriaxone, Cefuroxime, Erythromycin, Cefoxitin, Gentamicin, Imipenem, Linezolid, Meropenem, Norfloxacin, Piperacillin, Penicillin and Vancomycin were evaluated by the Agar-disc-diffusion method. The highest resistance of the studied pathogens to antimicrobials was seen against Azithromycin (100%) and Penicillin (100%) whereas the isolates were highly sensitive to Norfloxacin, Vancomycin, Linezolid and Cefoxitin. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 11-14